Investigation of the magnetic structure of the charge transfer compound CuTCNQ - Dr Ian Terry; Dr Pascal Manuel; Dr Adam Berlie; Dr Marek Szablewski (ISIS Facility, 2019)
Organic materials are playing an increasingly important role in electronic devices. An area of device technology where organics may make an impact is as memresistors, possibly in resistive random access memories . One material with potential is the charge transfer compound CuTCNQ (TCNQ = 7,7,8,8, -Tetracyanoquinodimethane), which exhibits electrical switching between low and high resistance states. One structural form of this material also exhibits magnetic order at low temperatures, the magnetism being associated with free radical electrons on the TCNQ molecules. The main goal of the proposed work is to use neutron scattering to identify the type of magnetic order that exists in the material. Neutron diffraction patterns will be recorded in the magnetically ordered phase and at a high temperature to look for intensity changes indicating the structure of the free radical magnetism.
Keywords: STFC ISIS Neutron and Muon Data